CHEMORADIOTHERAPY FOR ORAL CANCER USING HYPERFRACTIONATED RADIATION SCHEDULE - M. U. Radzhapova; I. A. Gulidov; F. E. Sevryukov; Yu. S. Mardynsky; J. A. Panaseykin; A. V. Semenov; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2021)
Purpose: to assess the efficacy and toxicity of concurrent  chemoradiotherapy with accelerated hyperfractionation in the treatment of  oral cancer. Material and Methods. A total of 79 patients with oral cancer were enrolled in this study. Accelerated hyperfractionated radiation therapy was administered using terabalt unit concurrently with two cycles of pF chemotherapy. The daily dose of 2.5 Gy was divided into two fractions of 1.0 Gy and 1.5 Gy which were delivered to high- and low-risk areas with 5–6-hour-interval between each treatment, 5 days per week to a total dose of 60.0 Gy and 50.0 Gy, respectively. Results. Complete response, partial response and stable disease were achieved in 63.3 %, 35.4 % and 1.3 % of and relapse-free survival rates for the entire group of patients were 54.5 % and 50.4 %, respectively. In the subgroup of patients with T3–4 stage tumors, the five-year overall survival rate was 50.8 %, and the five-year relapse-free survival rate was 47.2 %. Severe oral mucositis (grade 3) was noted in 36.7 % of patients. Grade 1 dermal toxicity was observed in 85 % of patients who experienced radiation-induced skin reactions. In 8.9 % of patients, osteoradionecrosis of the mandible occurred. All the patients included in the study completed the course of chemoradiotherapy as planned. Conclusion. Concurrent chemoradiotherapy with accelerated hyperfractionation (1.0 Gy + 1.5 Gy) appears to be an effective treatment option for oral cavity cancer patients in whom surgery is contraindicated.